Analysis of the Production Potential of Forest Products and Income for Community Groups in the Moyo Satonda National Park - Muslihuddin Aini; Zia Zannititah Pawana; Muhammad Yusri; Kurniasaputra; Didik Firmansyah Yamin; Paskah Roeliesto Leosae (Fakultas Kehutanan, Universitas Hasanuddin, 2026)
This study examines the production potential and income of buffer communities around Moyo Satonda National Park, West Nusa Tenggara. Five groups were analyzed: sesame, cashew, wild honey, marine tourism, and ecotourism. Data were collected through focus group discussions, interviews, observations, and documentation; descriptive analysis used triangulation. Findings show that sesame and cashew are the backbone of household economies, providing the highest production and income. Meanwhile, wild honey, marine tourism, and ecotourism act as livelihood diversification, reducing dependence on single commodities and supporting sustainable practices. This pattern reflects community-based conservation and sustainable livelihood frameworks, highlighting local participation in resource management with economic benefits. Socio-economic impacts include improved welfare and reduced reliance Socio-economic impacts include improved welfare and reduced reliance on forest encroachment, unsustainable forest resource extraction, wildlife hunting, and other environmentally damaging practices. Remaining challenges involve limited market access, basic post-harvest technology, and weak group management. The study recommends capacity building, broader market access and branding, supportive policies, and integrated diversification to strengthen community resilience and ensure ecosystem sustainability.